Current perspectives on neuromodulation in ALS patients: A systematic review and meta-analysis. - Ana M Jiménez-García; Gaspard Bonnel; Alicia Álvarez-Mota; Natalia Arias (PLoS ONE)
Amyotrophic Lateral Sclerosis (ALS) is a progressive neurodegenerative disease that affects motor neurons, resulting in muscle weakness, paralysis, and eventually patient mortality. In recent years, neuromodulation techniques have emerged as promising potential therapeutic approaches to slow disease progression and improve the quality of life of ALS patients. A systematic review was conducted until August 8, 2023, to evaluate the neuromodulation methods used and their potential in the treatment of ALS. The search strategy was applied in the Cochrane Central database, incorporating results from other databases such as PubMed, Embase, CTgov, CINAHL, and ICTRP. Following the exclusion of papers that did not fulfil the inclusion criteria, a total of 2090 records were found, leaving a total of 10 studies. R software was used to conduct meta-analyses based on the effect sizes between the experimental and control groups. This revealed differences in muscle stretch measures with manual muscle testing (p = 0.012) and resting motor threshold (p = 0.0457), but not with voluntary isometric contraction (p = 0.1883). The functionality of ALS was also different (p = 0.007), but not the quality of life. Although intracortical facilitation was not seen in motor cortex 1 (M1) (p = 0.1338), short-interval intracortical inhibition of M1 was significant (p = 0.0001). BDNF showed no differences that were statistically significant (p = 0.2297). Neuromodulation-based treatments are proposed as a promising therapeutic approach for ALS that can produce effects on muscle function, spasticity, and intracortical connections through electrical, magnetic, and photonic stimulation. Photobiomodulation stands out as an innovative approach that uses specific wavelengths to influence mitochondria, with the aim of improving mitochondrial function and reducing excitotoxicity. The lack of reliable placebo controls and the variation in stimulation frequency are some of the drawbacks of neuromodulation.